Analisis Kausalitas Belanja Pertahanan dan Pertumbuhan Ekonomi di Indonesia - Bayu Rahmadi Putra; Yeniwati Yeniwati; Melti Roza Adry (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2019)
This study aims to determine and analyze the causality between defense spending and economic growth in Indonesia. Data analysis used is descriptive analysis and inductive analysis. In the inductive analysis using the VAR approach, there are several tests, namely: (1) Test Stationaryity; (2) Cointegration Test; (3) Optimal Lag Determination; (4) Granger Causality Test; (5) Impulse Response Function; (6) Variance Decomposition. Research results show that: There is no causal relationship between defense spending and economic growth in Indonesia. However, there is a direct relationship of defense spending to economic growth.